Gender perception of pareidolia faces in emergency department patients: the influence of physician gender - Çamcı, Melih; Akdeniz, Gülsüm; Demirci, Harun; Demir Ünal, Esra; Altuntaş, Nilgün (Frontiers in Human Neuroscience, 2025)
BackgroundThe assessment of gender perception influenced by ambiguous facial cues in patients requiring emergency medical attention remains ambiguous. Pareidolia faces represent unconscious errors in facial recognition, wherein a wide array of visual attributes contribute to the interpretation of facial features. This study aims to explore the mechanisms underlying gender perception in individuals undergoing emergency medical treatment, employing an innovative digital pareidolia assessment to evaluate gender perception within the context of face pareidolia.MethodsFifty adult patients treated by a female physician in the green triage zone participated in the study. Target images consisted of face pareidolia images, while non-target images were scrambled. All images were standardized for size, tone, and light intensity. Patients instructed the pareidolia images and were asked if they discerned a face; if they answered ‘No,’ the next image was shown. If they saw a face, they identified the associated gender. Their responses and reaction times were systematically recorded digitally.ResultsOur findings revealed that, regardless of wait times, patients were significantly more likely to identify pareidolia faces as male rather than female, especially after being examined by a female physician. Additionally, male patients exhibited slightly longer reaction times than females when responding to pareidolia images.ConclusionThe outcomes of this investigation provide critical insights into the influence of pareidolia on gender perception of faces in the emergency department setting. It underscores the notion that gender biases, which arise from both biological and sociocultural factors, can affect the dynamics of patient-physician interactions.